Digital Business Adoption 2013-2018 A Bibliometric Study - Kresnha Reza, Heru; Susanti, Melly (CV. Inara, 2022)
Evaluating changes in the field of research on business adoption of digitalization is very useful to know the direction and topics of research during a certain period. This information can quickly identify the most influential research variables and become research updates. So far, we have not come across any research on digital business adoption over the past decade. Therefore, bibliometric mapping will be of great benefit to readers and can help convert publication metadata into maps or visualizations. The data is obtained from the publish or perish 7 application and then exported to the Mendeley application. We select articles and reviews published in Scopus indexed journals to be processed through VOSviewer. To describe 4665 terms with a minimum number of 7 occurrences in one term and 184 terms. A relevance score will be calculated based on the 30 most relevant terms. The results were found that from 2015 to 2020, there were 65089 total publications involved in the annual list and 30 terms were taken which are variables of digital business adoption. The most frequently repeated terms from the 4 clusters are Customer and Government with the same relevance score of 8571, Bitcoin with a relevance score of 83333, Firm with a relevance score of 7273, efficiency with a relevance score of 3333, experience with a relevance score of 2222.